Carbon nanotube dispersion
Patent Information
- Application Number
- JP2023131559
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-10
- Publication Date
- 2025-02-21
AI Technical Summary
【0014】 本発明によれば、分散状態の経時安定性に優れるとともに、導電性に優れる成形体を形成可能なカーボンナノチューブ分散液を提供することができる。
Smart Images

Figure 2025026159000001 
Figure 2025026159000002 
Figure 2025026159000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a carbon nanotube dispersion liquid. [Background technology]
[0002] 2. Description of the Related Art Carbon nanotubes (hereinafter sometimes abbreviated as "CNTs") have been attracting attention as a material that has excellent properties such as electrical conductivity, thermal conductivity, and strength.
[0003] Although each CNT has excellent properties, it is easy to bundle (become a bundle) due to van der Waals force due to its small outer diameter. Therefore, it has been conventional to prepare a carbon nanotube dispersion (CNT dispersion) by dispersing CNTs in a solvent. The obtained CNT dispersion is used, for example, for the production of a molded product such as a carbon film formed by an assembly of multiple CNTs, or an electrode for a secondary battery.
[0004] Therefore, in recent years, attempts have been made to improve the properties of the molded body by improving the CNT dispersion liquid. For example, Patent Document 1 discloses a CNT dispersion that contains CNTs, a solvent, and a dispersant, and in which the average outer diameter of the CNTs, the half-width of the peak at a diffraction angle 2θ=25°±2°, and the G / D ratio are each within a predetermined range. According to Patent Document 1, the use of the CNT dispersion makes it possible to obtain a resin composition, an electrode film, and the like that are excellent in electrical conductivity. Patent Document 2 discloses a CNT dispersion that contains CNTs, a dispersant, and a solvent, and in which the average outer diameter, BET specific surface area, and average fiber length of the CNTs are each within a predetermined range. According to Patent Document 2, the use of the CNT dispersion makes it possible to obtain a resin composition, an electrode film, and the like that are excellent in electrical conductivity and adhesion. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2020 / 004095 [Patent Document 2] Patent Publication No. 2021-72279 Summary of the Invention [Problem to be solved by the invention]
[0006] However, in recent years, there has been a demand for further improvement in the properties of molded articles formed from CNT dispersions, and the conventional CNT dispersions have room for improvement in terms of further increasing the electrical conductivity of the molded articles and in terms of the stability of the dispersed state over time.
[0007] Therefore, an object of the present invention is to provide a carbon nanotube dispersion liquid that has excellent stability over time in the dispersed state and is capable of forming a molded body having excellent electrical conductivity. [Means for solving the problem]
[0008] The present inventors have conducted intensive research with the aim of solving the above problems. Here, the present inventors have focused on bundles formed by the aggregation of multiple CNTs in a CNT dispersion (hereinafter, sometimes referred to as "CNT bundles"). The present inventors have found that in a CNT dispersion containing multiple CNTs containing single-walled CNTs, a solvent, and a thickener, if the average length of the CNT bundles is greater than a predetermined value, the average diameter of the CNT bundles is less than a predetermined value, and the ratio of CNT bundles having a diameter of more than 30.0 nm is less than a predetermined value, a CNT dispersion that is excellent in the stability over time of the dispersion state and can increase the conductivity of a molded body can be obtained, and have completed the present invention.
[0009] That is, an object of the present invention is to advantageously solve the above problems, and according to the present invention, the following CNT dispersion liquids [1] to [4] are provided.
[0010] [1] A carbon nanotube dispersion comprising a plurality of carbon nanotubes, a solvent, and a thickener, wherein the plurality of carbon nanotubes include single-walled carbon nanotubes, at least a portion of the plurality of carbon nanotubes form carbon nanotube bundles, the carbon nanotube bundles have an average length of more than 1.50 μm, an average diameter of the carbon nanotube bundles is 16.0 nm or less, and the number of carbon nanotubes having a diameter of more than 30.0 nm out of 100 carbon nanotubes in the carbon nanotube bundles is 15 or less. A CNT dispersion containing multiple CNTs, including single-walled CNTs, a solvent, and a thickener, in which the average length of the CNT bundles exceeds a predetermined value, the average diameter of the CNT bundles is equal to or less than a predetermined value, and the number of CNTs having a diameter of more than 30.0 nm out of 100 CNT bundles is equal to or less than a predetermined value, has excellent stability of the dispersed state over time, and can provide a conductive film with excellent conductivity. In the present invention, the "average length of carbon nanotube bundles," the "average diameter of carbon nanotube bundles," and the "number of carbon nanotube bundles with a diameter of more than 30.0 nm out of 100 carbon nanotube bundles" can each be measured using the method described in the examples of this specification.
[0011] [2] The carbon nanotube dispersion liquid according to [1] above, wherein the carbon nanotube bundles have an average aspect ratio of more than 100. When the average aspect ratio of the CNT bundles exceeds 100, the stability over time of the dispersed state of the CNT dispersion liquid can be further improved, and the electrical conductivity of the molded article can be further increased. In the present invention, the "average aspect ratio" of a CNT bundle can be determined by calculating the ratio of the average length to the average diameter of the CNT bundle (average length / average diameter).
[0012] [3] The carbon nanotube dispersion liquid according to [1] or [2] above, wherein the G / D ratio of the carbon nanotubes is 0.5 or more and 120 or less. If the G / D ratio of the CNTs is within the above range, the stability over time of the dispersed state of the CNT dispersion liquid can be further improved, and the electrical conductivity of the molded article can be further increased. In the present invention, the "G / D ratio" refers to the ratio of the G band peak intensity to the D band peak intensity in a Raman spectrum, and can be measured by the method described in the Examples of this specification.
[0013] [4] The carbon nanotube dispersion liquid according to any one of the above [1] to [3], wherein the thickener comprises at least one selected from the group consisting of a cellulose-based polymer, a polycarboxylic acid, and a polyvinylpyrrolidone. When the thickener contains at least one selected from a cellulose-based polymer, a polycarboxylic acid, and a polyvinylpyrrolidone, the stability of the dispersed state of the CNT dispersion over time can be further improved, and the electrical conductivity of the molded article can be further increased. Effect of the Invention
[0014] According to the present invention, it is possible to provide a carbon nanotube dispersion liquid which is excellent in the stability of the dispersed state over time and is capable of forming a molded body having excellent electrical conductivity. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, an embodiment of the present invention will be described in detail. Here, the CNT dispersion liquid of the present invention is not particularly limited, and can be used, for example, as a material for forming a molded body such as a carbon membrane or an elastomer molded body, an electrode for a secondary battery, and the like.
[0016] (Carbon nanotube dispersion) The CNT dispersion of the present invention contains at least CNTs, a solvent, and a thickener, and optionally contains components other than the CNTs, the solvent, and the thickener (other components). At least a portion of the multiple CNTs are single-walled CNTs, and form CNT bundles in the CNT dispersion. Here, the CNT dispersion of the present invention is characterized in that the average length of the CNT bundles exceeds 1.50 μm, the average diameter of the CNT bundles is 16.0 nm or less, and the number of CNT bundles having a diameter of more than 30.0 nm is 15 or less out of 100 CNT bundles. It should be noted that the CNT bundle is formed by assembling a number of CNTs into a bundle (bundle) along the longitudinal direction of the CNTs.
[0017] In addition, since the CNT dispersion of the present invention has an average length of the CNT bundles exceeding a predetermined value, an average diameter of the CNT bundles not exceeding a predetermined value, and the number of CNT bundles with diameters exceeding 30.0 nm out of 100 bundles not exceeding a predetermined value, the CNT dispersion has excellent stability over time in the dispersed state, and can provide excellent electrical conductivity to the molded product. The reason why the above effects are obtained by using the CNT dispersion of the present invention is not clear, but is presumed to be as follows.
[0018] In order to improve the dispersibility of the CNT dispersion, the inventors focused on CNT bundles composed of multiple CNTs in the CNT dispersion. The smaller the average diameter of the CNT bundles, the fewer the number of CNTs constituting each bundle. Also, the fewer the number of CNT bundles with a diameter of more than 30.0 nm among 100 CNT bundles, the more the number of CNT bundles present in the CNT dispersion. And, in the CNT dispersion of the present invention, the average diameter of the CNT bundles is set to 16.0 nm or less, and the number of CNT bundles with a diameter of more than 30.0 nm among 100 CNT bundles is set to 15 or less, so that the number of CNT bundles present in the CNT dispersion is sufficiently secured. In addition, in the dispersion of the present invention, the average length of the CNT bundles exceeds 1.50 μm, so that the length of the CNT bundles present in the CNT dispersion is sufficiently secured. In a CNT dispersion in which the number and length of CNT bundles are sufficiently ensured, the CNTs are stably dispersed over time. Furthermore, by using such a CNT dispersion, CNT bundles of sufficient length can be distributed in the molded body, making it possible to form good conductive paths. For the reasons described above, it is believed that the CNT dispersion of the present invention has excellent stability of the dispersed state over time, and that the use of this CNT dispersion can enable a conductive film to exhibit excellent conductivity.
[0019] <cnt> The CNTs are not particularly limited as long as they contain single-walled CNTs. As the CNTs, only single-walled CNTs may be used, or a combination of single-walled CNTs and multi-walled CNTs may be used.
[0020] <<Properties>> [Average length of CNT bundle] The average length of the CNT bundle must be more than 1.50 μm, preferably 1.60 μm or more, more preferably 1.70 μm or more, even more preferably 1.80 μm or more, and particularly preferably 1.90 μm or more. If the average length of the CNT bundle is 1.50 μm or less, the conductivity of the molded body decreases. In addition, the upper limit of the average length of the CNT bundle is not particularly limited, and can be, for example, 3.50 μm or less, or 3.00 μm or less. The average length of the CNT bundles in the CNT dispersion can be adjusted, for example, by changing the length of the raw CNTs (CNTs used as raw materials when preparing the CNT dispersion) and the conditions of the dispersion process. For example, when a wet jet mill is used for the dispersion process, the average length of the CNT bundles decreases by increasing the pressure applied to the mixed liquid passing through the jet mill, and increases by decreasing the pressure. In addition, the average length of the CNT bundles in the CNT dispersion decreases by increasing the number of passes of the dispersion process using the wet jet mill (the number of times the entire amount of the mixed liquid passes through the wet jet mill), and increases by decreasing the number of passes.
[0021] [Average diameter of CNT bundles] The average diameter of the CNT bundle must be 16.0 nm or less, preferably 15.9 nm or less, more preferably 15.8 nm or less, and even more preferably 15.7 nm or less. If the average diameter of the CNT bundle exceeds 16.0 nm, the stability of the dispersion state of the CNT dispersion liquid over time decreases, and the conductivity of the obtained molded body decreases. In addition, the lower limit of the average diameter of the CNT bundle is not particularly limited, and can be, for example, 13.5 nm or more, or 14.0 nm or more. The average diameter of the CNT bundles in the CNT dispersion can be adjusted, for example, by changing the diameter of the raw CNTs and the conditions of the dispersion process. For example, when a wet jet mill is used for the dispersion process, the average diameter of the CNT bundles decreases by increasing the pressure applied to the mixed liquid passing through the wet jet mill, and increases by decreasing the pressure. In addition, the average diameter of the CNT bundles in the CNT dispersion decreases by increasing the number of passes of the dispersion process using the wet jet mill, and increases by decreasing the number of passes.
[0022] [Number of CNT bundles with diameters over 30.0 nm] The number of CNT bundles having a diameter of more than 30.0 nm must be 15 or less, preferably 14 or less, more preferably 13 or less, even more preferably 12 or less, even more preferably 11 or less, and particularly preferably 10 or less. If the number of CNT bundles having a diameter of more than 30.0 nm is more than 15, the stability of the dispersion state of the CNT dispersion over time decreases, and the conductivity of the resulting molded body decreases. In addition, the lower limit of the number of CNT bundles having a diameter of more than 30.0 nm is not particularly limited, and can be, for example, 1 or more, or 2 or more. The number of CNT bundles with diameters exceeding 30.0 nm can be adjusted, for example, by changing the length or diameter of the raw CNTs and the conditions of the dispersion process. For example, when a wet jet mill is used for the dispersion process, increasing the pressure applied to the mixed liquid passing through the wet jet mill reduces the number of CNT bundles with diameters exceeding 30.0 nm, and decreasing the pressure increases the number. In addition, increasing the number of passes of the dispersion process using the wet jet mill reduces the number of CNT bundles with diameters exceeding 30.0 nm, and decreasing the number increases the number.
[0023] [Average aspect ratio of CNT bundles] The average aspect ratio of the CNT bundle is preferably more than 100, more preferably 110 or more, even more preferably 120 or more, and particularly preferably 125 or more. If the average aspect ratio of the CNT bundle is more than 100, the stability of the dispersion state of the CNT dispersion over time can be further improved, and the conductivity of the molded body can be further increased. In addition, the upper limit of the average aspect ratio of the CNT bundle is not particularly limited, and can be, for example, 250 or less, 225 or less, or 200 or less.
[0024] [G / D ratio] The G / D ratio of the CNTs is preferably 0.5 or more, more preferably 1 or more, and is preferably 120 or less, more preferably 110 or less, even more preferably 95 or less, even more preferably 70 or less, even more preferably 45 or less, and particularly preferably 20 or less. If the G / D ratio of the CNTs is within the above-mentioned range, the stability over time of the dispersed state of the CNT dispersion can be further improved, and the conductivity of the molded body can be further increased.
[0025] <<Content ratio>> The content of CNT in the CNT dispersion is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, more preferably 2% by mass or less, more preferably 1% by mass or less, and even more preferably 0.5% by mass or less, based on the total amount of the CNT dispersion being 100% by mass. If the proportion of CNT in the CNT dispersion is 0.01% by mass or more, the conductivity of the molded body can be further increased and the productivity of the molded body can be improved. On the other hand, if the proportion of CNT in the CNT dispersion is 2% by mass or less, the stability of the dispersion state of the CNT dispersion over time can be further improved.
[0026] <Solvent> The CNT dispersion of the present invention may contain only water as a solvent, may contain only an organic solvent (e.g., esters, ketones, alcohols) as a solvent, or may be a mixture of water and an organic solvent. From the viewpoint of further improving the stability of the dispersion state of the CNT dispersion over time while further increasing the conductivity of the molded body, it is preferable that the CNT dispersion of the present invention contains water as a solvent. The CNT dispersion of the present invention may contain one type of organic solvent, or may contain two or more types of organic solvents.
[0027] Here, the CNT dispersion of the present invention preferably has a water ratio in the solvent of 70 mass% or more, more preferably 90 mass% or more, even more preferably 99 mass% or more, and particularly preferably 100 mass% (i.e., the CNT dispersion of the present invention contains only water as a solvent), with the total amount of the solvent being 100 mass%. If the water ratio in the solvent in the CNT dispersion is equal to or more than the lower limit, the stability over time of the dispersion state of the CNT dispersion can be further improved, and the conductivity of the molded body can be further increased.
[0028] <Thickener> The thickener is not particularly limited and may be any known thickener, and may be, for example, a water-soluble polymer such as a cellulose-based polymer, polycarboxylic acid, polyvinylpyrrolidone, polyvinyl alcohol, polyacrylamide, or polyimide. In the present invention, a polymer is "water-soluble" means that when 0.5 g of the polymer (solid content) is dissolved in 100 g of water at 25°C, the amount of insoluble matter is less than 10.0 mass %.
[0029] Cellulosic polymers include, for example, carboxymethylcellulose, methylcellulose, hydroxypropylmethylcellulose, hydroxyethylmethylcellulose, and salts and derivatives thereof. Polycarboxylic acids include, for example, polyacrylic acid, polymethacrylic acid, alginic acid, and salts and derivatives thereof. Examples of the water-soluble vinyl polymer include polyvinylpyrrolidone, polyvinyl alcohol, polyvinyl methyl ether, poly-N-vinyl acetamide, polyacrylamide, and polyimide. Here, examples of the salt include alkali metal salts such as sodium salts, ammonium salts, etc. Examples of the derivative include esters such as alkyl esters, and ethers.
[0030] The above-mentioned thickeners may be used alone or in any combination of two or more at any ratio. Among these, from the viewpoint of further improving the stability over time of the dispersion state of the CNT dispersion and further increasing the conductivity of the molded body, the thickeners are preferably cellulose-based polymers, polycarboxylic acids, and polyvinylpyrrolidone, and more preferably carboxymethylcellulose and its salts, polyacrylic acid and its salts, and polyvinylpyrrolidone.
[0031] <<Weight average molecular weight>> The weight average molecular weight of the thickener is preferably 5,000 or more, more preferably 10,000 or more, and is preferably 1,000,000 or less, and more preferably 500,000 or less. If the weight average molecular weight of the thickener is 5,000 or more, the dispersibility of CNTs in the CNT dispersion can be improved. Also, if the weight average molecular weight of the thickener is 1,000,000 or less, the viscosity increase of the CNT dispersion can be suppressed. In the present invention, the "weight average molecular weight" can be measured using gel permeation chromatography and expressed as a standard polystyrene equivalent value.
[0032] <<Content ratio>> The proportion of the thickener contained in the CNT dispersion is preferably 0.1% by mass or more, more preferably 0.2% by mass or more, preferably 10% by mass or less, more preferably 5% by mass or less, still more preferably 2% by mass or less, and particularly preferably 1% by mass or less, with the total amount of the CNT dispersion being 100% by mass. If the proportion of the thickener in the CNT dispersion is within the above-described range, the temporal stability of the dispersion state of the CNT dispersion can be further improved, and the conductivity of the molded body can be further enhanced.
[0033] The content of the thickener in the CNT dispersion is preferably 100 parts by mass or more, more preferably 200 parts by mass or more, still more preferably 300 parts by mass or more, preferably 500 parts by mass or less, and more preferably 450 parts by mass or less per 100 parts by mass of CNT. If the amount ratio of the thickener to CNT in the CNT dispersion is within the above-described range, the temporal stability of the dispersion state of the CNT dispersion can be further improved, and the conductivity of the molded body can be further enhanced.
[0034] <Other components> Examples of other components that the CNT dispersion may optionally contain include conductive materials other than CNT, polymer components other than the above-described thickener, antioxidants, resins, and the like. Note that the CNT dispersion may contain only one type of other component or may contain two or more types of other components. The proportion of other components contained in the CNT dispersion is preferably 5% by mass or less, more preferably 1% by mass or less, still more preferably 0.5% by mass or less, even more preferably 0.1% by mass or less, and particularly preferably 0% by mass (that is, the CNT dispersion of the present invention does not contain other components), with the total amount of the CNT dispersion being 100% by mass.
[0035] <Preparation of CNT dispersion> The CNT dispersion of the present invention can be prepared, for example, by subjecting a mixture containing the above-mentioned CNT, a solvent, a thickener, and any other components to a dispersion treatment. The dispersion treatment is not particularly limited, and can be performed using a mixer such as a wet jet mill, a bead mill, a ball mill, a sand mill, a pigment disperser, a crusher, an ultrasonic disperser, a homogenizer, a planetary mixer, or a Filmix. Among them, it is preferable to use a wet jet mill from the viewpoint of further improving the stability of the dispersion state of the CNT dispersion over time while further increasing the conductivity of the molded body. Examples of wet jet mills include "NanoVeita (registered trademark)" (manufactured by Yoshida Machine Co., Ltd.), "BERYU SYSTEM PRO" (manufactured by Biryu Co., Ltd.), ultra-high pressure wet atomizer (manufactured by Yoshida Kogyo Co., Ltd.), "Nanomizer (registered trademark)" (manufactured by Nanomizer Co., Ltd.), and "Starburst (registered trademark)" (manufactured by Sugino Machine Co., Ltd.).
[0036] Here, examples of the nozzles equipped in the wet jet mill include a straight nozzle and a cross nozzle. The straight nozzle has an I-shaped nozzle cross section and requires relatively small processing energy. On the other hand, the cross nozzle has an X-shaped nozzle cross section and requires larger processing energy than the straight nozzle. From the viewpoint of further improving the stability over time of the dispersion state of the CNT dispersion and further increasing the conductivity of the molded body, it is preferable to use a straight nozzle as the nozzle equipped in the wet jet mill.
[0037] Here, the pressure applied during the dispersion treatment of the mixed liquid by the wet jet mill is preferably 10 MPa or more, more preferably 15 MPa or more, even more preferably 20 MPa or more, and preferably 200 MPa or less, more preferably 150 MPa or less, and even more preferably 100 MPa or less. If the pressure applied to the mixed liquid is 10 MPa or more, the stability of the dispersion state of the CNT dispersion over time can be further improved and the conductivity of the resulting molded body can be further increased. In addition, if the pressure applied to the mixed liquid is 200 MPa or less, the cutting of the CNTs due to the dispersion treatment can be suppressed, thereby further increasing the conductivity of the resulting molded body.
[0038] In addition, the number of passes of the dispersion treatment by the wet jet mill is preferably 10 or more, more preferably 15 or more, even more preferably 20 or more, and preferably 100 or less, more preferably 80 or less, and even more preferably 60 or less. If the number of passes of the dispersion treatment by the wet jet mill is 10 or more, the stability of the dispersion state of the CNT dispersion over time can be further improved and the conductivity of the obtained molded body can be further increased. In addition, if the number of passes of the dispersion treatment by the wet jet mill is 100 or less, the cutting of the CNTs due to the dispersion treatment can be suppressed, thereby further increasing the conductivity of the obtained molded body and sufficiently ensuring the manufacturing efficiency of the CNT dispersion. EXAMPLES
[0039] The present invention will be specifically described below based on examples, but the present invention is not limited to these examples. In the following description, "%" and "parts" expressing amounts are based on mass unless otherwise specified. In the examples and comparative examples, the average length, average diameter, average aspect ratio, and number of CNT bundles with a diameter exceeding 30.0 nm, the G / D ratio of the CNTs, the rate of change in particle size and the rate of change in viscosity, and the volume conductivity of the carbon film (molded body) were evaluated by the following methods.
[0040] <Average length, average diameter, average aspect ratio> The CNT dispersions prepared in the examples and comparative examples were diluted with pure water so that the concentration of CNTs became 25 ppm by mass. After dropping one drop of the obtained diluted solution onto a wafer with a dropper, the wafer was placed on a hot plate heated to 90 °C and baked for 1 minute. The obtained CNT-coated wafer was observed using a scanning electron microscope (SEM, manufactured by Hitachi High-Technologies Corporation, product name "SU8200") under the conditions of a working distance of 3 mm, an acceleration voltage of 1.0 kV, and a magnification of 10,000 times, and a plurality of SEM images containing 10 or more CNT bundles in the field of view were acquired. For 100 CNT bundles arbitrarily extracted from the obtained SEM images, the diameter (outer diameter) and length of the bundles were measured. Then, the arithmetic mean value of the diameters of the 100 measured CNT bundles was defined as the average diameter (nm) of the CNT bundles in the CNT dispersion. Also, the arithmetic mean value of the lengths of the 100 measured CNT bundles was defined as the average length (μm) of the CNT bundles in the CNT dispersion. The average aspect ratio was calculated by dividing the average length (nm) by the average diameter (nm). <Number of CNT bundles with a diameter exceeding 30.0 nm> As described above, the diameters (outer diameters) of 100 CNT bundles were measured and evaluated according to the following criteria. A: The number of bundles with a diameter exceeding 30.0 nm is 10 or less B: The number of bundles with a diameter exceeding 30.0 nm is 11 or more and 15 or less C: The number of bundles with a diameter exceeding 30.0 nm is 16 or more <G / D ratio> Using a microscopic Raman spectrophotometer (manufactured by Thermo Fisher Scientific, product name "Nicolet Almega XR"), the Raman spectra of the CNTs used in the examples and comparative examples were measured. Then, for the obtained Raman spectra, the intensity of the G-band peak observed in the vicinity of 1590 cm -1 and the intensity of the D-band peak observed in the vicinity of 1340 cm -1 were determined, and the G / D ratio was calculated. <Temporal stability of the dispersion state> If both the "rate of change in particle size" and "rate of change in viscosity" shown below are rated A or B, it means that the CNT dispersion has excellent stability of the dispersed state over time. [Particle size change rate] The average particle diameter (D50) value immediately after preparation and the average particle diameter (D50) value 10 days after preparation were measured for the CNT dispersions obtained in the examples and comparative examples. The average particle diameter (D50) was measured by diluting the aqueous dispersion with water to a CNT concentration of 0.04% with a laser diffraction / scattering particle size distribution measuring device (manufactured by HORIBA, product name "Partica LA-960V2"), and the particle diameter at which the cumulative volume calculated from the small diameter side is 50% in the obtained particle size distribution (volume basis) was determined as the average particle diameter (μm). The measurement conditions were as follows. Circulation speed: 3, Ultrasonic intensity: 7, Ultrasonic time: 1 min, Stirring speed: 1, Stirring mode: Continuous (Circulation / Ultrasonic operating conditions) Ultrasonic intensity 7, ultrasonic time 5 seconds (ultrasonic operation during air evacuation) Refractive index of water: 1.333 Refractive index of carbon material: 1.92 The average particle diameter (D50) value immediately after preparation was taken as d0 (μm), and the average particle diameter (D50) value 10 days after preparation was taken as d1 (μm), and the particle diameter change rate (%) was calculated from the equation: Particle diameter change rate (%) = [(d1-d0) / d0] x 100, and evaluated according to the following criteria. The smaller the particle diameter change rate value, the less likely the CNT dispersion state is to change, i.e., the more excellent the stability of the dispersion state over time is. A: Particle size change rate is less than 1% B: Particle size change rate is 1% or more and less than 30% C: Particle size change rate is 30% or more [Viscosity change rate] For the CNT dispersion liquids obtained in the examples and comparative examples, the viscosity values immediately after preparation and the viscosity values 10 days after preparation were measured respectively. Each viscosity measurement was carried out at a temperature of 20 °C using a rheometer (manufactured by Anton Paar, product name "MCR-102"). Specifically, a cone plate was used as the measurement jig, the range of shear rate from 100 to 9000 (1 / s) was measured, and the viscosity (mPa·s) at a shear rate of 1000 (1 / s) was determined. Then, taking the viscosity value immediately after preparation as η0 (mPa·s) and the viscosity value 10 days after preparation as η1 (mPa·s), the viscosity change rate (%) = [(η1 - η0) / η0] × 100 was used to calculate the viscosity change rate (%), and the evaluation was carried out according to the following criteria. The smaller the value of the viscosity change rate, the more difficult it is for the CNT dispersion liquid to thicken over time, that is, it means that the dispersion state has excellent temporal stability. A: Viscosity change rate is less than 10% B: Viscosity change rate is 10% or more and less than 20% C: Viscosity change rate is 20% or more <Volume conductivity> The volume conductivity (S / cm) of the carbon films (formed bodies) prepared in the examples and comparative examples was measured in accordance with JIS K 7194 using a low resistivity meter (manufactured by Mitsubishi Chemical Analytech Co., Ltd., product name "Roresta-GX"), and the evaluation was carried out according to the following criteria. The higher the value of this volume conductivity, the more excellent the carbon film (formed body) is in conductivity. A: Value of volume conductivity is 100 S / cm or more B: Value of volume conductivity is 50 S / cm or more and less than 100 S / cm C: Value of volume conductivity is less than 50 S / cm
[0041] (Example 1) <Preparation of CNT dispersion liquid> [Synthesis of CNT] Single-walled CNTs (hereinafter referred to as "CNT-a") were produced according to the method disclosed in Example 4 of International Publication No. 2022 / 114237. The properties of the obtained CNT-a were: G / D ratio: 1.2, tapped bulk density: 0.02 g / cm 3 , average CNT length: 150 μm, BET specific surface area: 600 m 2 / g, average outer diameter: 4.0 nm, carbon purity 99.0 mass%. [Preparation of CNT dispersion] 0.3 g of CNT-a (G / D ratio: 1.2) as the single-walled CNT obtained above was added to 300 mL of an aqueous solution (concentration of sodium carboxymethylcellulose: 0.4%) containing sodium carboxymethylcellulose (manufactured by Tokyo Chemical Industry Co., Ltd., product code "C0045"; average degree of polymerization: 500) as a thickener in water as a solvent, to obtain a mixed liquid (concentration of single-walled CNT: 0.1%). A dispersion treatment was performed on this mixed liquid using a wet jet mill (manufactured by Yoshida Kikai Kogyo Co., Ltd., model number "NVL-ES008A-D10", product name "Nano Vaita (registered trademark)") under conditions of a pressure of 25 MPa and a number of passes of 40. Specifically, a shear force was applied to the mixed liquid while applying back pressure to disperse the single-walled CNT, and a CNT dispersion liquid was obtained. The average length, average diameter, and average aspect ratio of the CNT bundles, the number of CNT bundles with a diameter of more than 30.0 nm, as well as the rate of change in particle size and the rate of change in viscosity were measured for the obtained CNT dispersion. The results are shown in Table 1. <Preparation of carbon film (molded body)> The CNT dispersion liquid prepared above was filtered under a condition of 0.09 MPa using a vacuum filtration device equipped with a membrane filter. After the filtration was completed, the carbon film formed on the membrane filter was washed by passing isopropyl alcohol and water through the vacuum filtration device, and then air was passed through for 15 minutes. Next, the carbon film / membrane filter was immersed in ethanol, and the carbon film was peeled off from the membrane filter to obtain a carbon film as a molded body. The obtained carbon film was the same size as the membrane filter and had excellent film forming properties, and even when peeled off from the filter, it maintained its film state and had excellent self-supporting properties. The volume conductivity of this carbon film was measured. The results are shown in Table 1.
[0042] (Examples 2 to 11, Comparative Examples 1 to 8) A CNT dispersion was prepared and a carbon film was produced in the same manner as in Example 1, except that the pressure and number of passes in the dispersion treatment using a wet jet mill were changed as shown in Tables 1 to 3 during the preparation of the CNT dispersion. Evaluations were then performed in the same manner as in Example 1. The results are shown in Tables 1 to 3. In Comparative Example 8, the dispersibility of CNTs in the CNT dispersion was extremely low, and the average length and average diameter of the CNT bundles could not be measured.
[0043] Example 12 During preparation of the CNT dispersion, CNT-b (manufactured by Zeon Corporation, product name "ZEONANO (registered trademark) SG101"; G / D ratio: 5.0) was used instead of CNT-a as single-walled CNT, and the pressure and number of passes in the dispersion treatment using a wet jet mill were changed as shown in Table 2. Except for this, the preparation of the CNT dispersion and the production of the carbon film were carried out in the same manner as in Example 1. Then, evaluation was carried out in the same manner as in Example 1. The results are shown in Table 2.
[0044] Example 13 During preparation of the CNT dispersion, sodium polyacrylate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., product code "196-02955"; degree of polymerization: 22,000 to 70,000) was used instead of sodium carboxymethylcellulose as a thickener, and the pressure and number of passes in the dispersion treatment using a wet jet mill were changed as shown in Table 2. Except for this, the synthesis of CNTs, the preparation of a CNT dispersion, and the production of a carbon film were carried out in the same manner as in Example 1. Evaluations were then carried out in the same manner as in Example 1. The results are shown in Table 2.
[0045] Example 14 During preparation of the CNT dispersion, polyvinylpyrrolidone (manufactured by Nippon Shokubai Co., Ltd., product name "Polyvinylpyrrolidone-K30"; HLB value: 15) was used instead of sodium carboxymethylcellulose as a thickener, and the pressure and number of passes in the dispersion treatment using a wet jet mill were changed as shown in Table 2. Except for this, the synthesis of CNTs, the preparation of a CNT dispersion, and the production of a carbon film were carried out in the same manner as in Example 1. Evaluations were then carried out in the same manner as in Example 1. The results are shown in Table 2.
[0046] (Examples 15 to 17) During preparation of the CNT dispersion, CNT-c (manufactured by OCSiAl, product name "Tuball (registered trademark)"; G / D ratio: 109) was used instead of CNT-a as the single-walled CNT, and the pressure and number of passes in the dispersion treatment using the wet jet mill were changed as shown in Table 2. Except for this, the preparation of the CNT dispersion and the production of the carbon film were carried out in the same manner as in Example 1. Then, evaluation was carried out in the same manner as in Example 1. The results are shown in Table 2.
[0047] (Examples 18 to 19) During preparation of the CNT dispersion, CNT-d (manufactured by Meijo Nano Carbon Co., Ltd., product name "MEIJO eDIPS (registered trademark)"; G / D ratio: 119) was used instead of CNT-a as single-walled CNT, and the pressure and number of passes in the dispersion treatment using the wet jet mill were changed as shown in Tables 2 and 3. Except for this, the preparation of the CNT dispersion and the production of the carbon film were carried out in the same manner as in Example 1. Then, evaluation was carried out in the same manner as in Example 1. The results are shown in Tables 2 and 3.
[0048] In addition, in Tables 1 to 3 shown below, "Single-walled" refers to single-walled CNTs; "CMC" stands for sodium carboxymethylcellulose; "PAA" stands for sodium polyacrylate; "PVP" refers to polyvinylpyrrolidone; "Number of CNT bundles with a diameter of more than 30 nm" indicates the number of CNT bundles with a diameter of more than 30.0 nm out of 100 CNT bundles. In addition, the "average aspect ratio of the CNT bundle" is expressed as a value rounded off to the first decimal place.
[0049] [Table 1]
[0050] [Table 2]
[0051] [Table 3]
[0052] As can be seen from Tables 1 to 3, in Examples 1 to 19 which used CNT dispersions containing single-walled CNTs, a solvent, and a thickener, in which the average length of the CNT bundles exceeded a predetermined value, the average diameter of the CNT bundles was equal to or less than a predetermined value, and the number of CNT bundles having a diameter of more than 30.0 nm out of 100 CNT bundles was equal to or less than a predetermined value, CNT dispersions with excellent stability of the dispersed state over time and carbon films with excellent electrical conductivity were produced. On the other hand, in Comparative Examples 1 to 3, in which the average diameter of the CNT bundles exceeds a predetermined value, and in Comparative Examples 4 to 6, in which the average length of the CNT bundles is equal to or shorter than a predetermined value, the conductivity of the carbon film is found to be reduced compared to Examples 1 to 19. In addition, in Comparative Example 7, in which the average diameter of the CNT bundles exceeds a predetermined value and the number of CNT bundles having a diameter exceeding 30.0 nm out of 100 CNT bundles exceeds a predetermined value, it is found that the stability of the dispersion state of the CNT dispersion over time and the conductivity of the carbon film are reduced compared to Examples 1 to 19. Furthermore, in Comparative Example 8, in which the number of CNT bundles with a diameter of more than 30.0 nm out of 100 CNT bundles exceeds a specified value, it can be seen that the stability of the dispersion state of the CNT dispersion over time and the conductivity of the carbon film are reduced compared to Examples 1 to 19. [Industrial Applicability]
[0053] According to the present invention, it is possible to provide a carbon nanotube dispersion liquid which is excellent in the stability of the dispersed state over time and is capable of forming a molded body having excellent electrical conductivity.< / cnt>
Claims
1. A carbon nanotube dispersion liquid containing a plurality of carbon nanotubes, a solvent, and a thickener, the plurality of carbon nanotubes includes single-walled carbon nanotubes; At least a portion of the plurality of carbon nanotubes form a carbon nanotube bundle; the average length of the carbon nanotube bundles is greater than 1.50 μm; The carbon nanotube bundle has an average diameter of 16.0 nm or less; The carbon nanotube dispersion liquid, wherein the number of carbon nanotubes having a diameter of more than 30.0 nm is 15 or less out of 100 carbon nanotubes in the carbon nanotube bundle.
2. The carbon nanotube dispersion of claim 1 , wherein the carbon nanotube bundles have an average aspect ratio of greater than 100.
3. The carbon nanotube dispersion according to claim 1 , wherein the G / D ratio of the carbon nanotubes is 0.5 or more and 120 or less.
4. 4. The carbon nanotube dispersion according to claim 1, wherein the thickener comprises at least one selected from the group consisting of a cellulose-based polymer, a polycarboxylic acid, and a polyvinylpyrrolidone.
Citation Information
Patent Citations
Carbon nanotube dispersion liquid for non-aqueous electrolyte secondary battery, resin composition using the same, mixture slurry, electrode film, and non-aqueous electrolyte secondary battery
JP2021072279A
Carbon nanotube dispersion and usage therefor
WO2020004095A1